Profil Risiko Penyakit Jantung Koroner (PJK) pada Wanita Premenopause menggunakan Rasio Profil Lipid - Mutmainnah Abbas; Olin Toyi; Julia F.N; Rosdiana Mus (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Premenopause is a transitional period between the reproductive period and the elderly which is physiological and occurs around age of 45-55 years. Conditions premenopause phase are caused by hormone changes, decreased levels of hormone estrogen. Hormone estrogen functions to regulate balance of body fat and maintain lipolysis in fat tissue and can also prevent in blood by increasing HDL cholesterol levels and reducing triglyceride levels. Atherogenic Index (IA) is a new marker to measure level of atherogenicity directly related to the risk of atherosclerosis calculated from the Log ratio (TG/HDL-c). This research aims to determine the risk profile of Coronary Heart Disease (CHD) in premenopausal women using lipid profile ratios. This study used an analytical method with a cross sectional approach. From 40 subjects who met research criteria, atherogenic index result in low risk category were 6 (15%) people, medium risk 21 (52.5%) people, and high risk 13 (32.5%) people. Based on the research it can be concluded the atherogenic index in premenopause women is 0.27 which the high risk.